From communities to individuals: Using remote sensing to inform and monitor woodland restoration. (30th December 2021) - Harrison, Peter A.; Camarretta, Nicolò; Krisanski, Sean; Bailey, Tanya G.; Davidson, Neil J.; Bain, Glen; Hamer, Rowena; Gardiner, Riana; Proft, Kirstin; Taskhiri, Mohammad Sadegh; Turner, Paul; Turner, Darren; et al.
Summary: The benefits of using remote sensing technologies for informing and monitoring ecological restoration of forests from the community to the individual are presented. At the community level, we link remotely sensed measures of structural complexity with animal behaviour. At the plot level, we monitor the return of vegetation structure and ecosystem services (e.g. carbon sequestration) using data‐rich three‐dimensional point clouds. At the individual‐level, we use high‐resolution images to accurately classify plants to species and provenance and show genetic‐based variation in canopy structural traits. To facilitate the wider use of remote sensing in restoration, we discuss the challenges that remain to be resolved.